Enhancing Gender Equality, Disability and Social Inclusion through Farmer Managed Natural Regeneration in Central Rift, Kenya - Too, Prisca; Chesire, Michael; Kigen, Charles; Korir, Janet; Munyao, Carol (International Journal of Environmental Sciences, 2025)
This paper examines how World Vision’s project “Central Rift Farmer-Managed Natural Regeneration Scale-up project (CRIFSUP)” carried out between 2017 and 2021 used Gender Equality, Disability and Social Inclusion (GEDSI) approach and transformation power relations among farmers. The Study areas were Ndabibi in Nakuru County, Marigat in Baringo County, and Ng’oswet in Elgeyo Marakwet. Methodology adopted was mixed method approach and data collected using collective brainstorming sessions with communities, key informant interviews, Household questionnaire, focused group discussions for adults and children, and observation. Purposive sampling was employed to identify farmers to participate in focus group discussions and key informants. Apart from examining the field reports on this project, this study reviewed secondary related literature. The theory of change and agency and employed to how the implementation of FMNR created a conducive environment for the transformation of gender, disability and social inclusion. Enhancement of gender, disability and social inclusion is traced by examining the changes that transpired between the time the baseline report was conducted, CRIFSUP GESI Report and the end of term report. The focus is on decision making, time use, roles, responsibilities and economic empowerment. The findings showed that the time spent on collecting firewood was reduced to 30 minutes. Energy saving measures such as jikos and biogas were introduced by CRIFSUP. Savings for transformation groups enabled women and people with disabilities to access resources that enabled them to diversify their roles and engage in income generating activities such as bee keeping. However, mainstreaming gender, disability and social inclusion considerations has been partially successful, for instance land ownership and access is still heavily weighted towards men and this affects women access and use of trees. This influences the time women spend to look for firewood.